Isolation of the Lipid Intermediate in Peptidoglycan Biosynthesis from Escherichia coli - Umbreit, Jay N. (1972)
The lipid intermediate in peptidoglycan biosynthesis was isolated from Escherichia coli strain W and characterized as C(55)-isoprenyl-pyrophosphoryl N-acetylmuramyl(-pentapeptide)-N-acetyl-glucosamine.